Applied fundamentals Guess the number - Dennison, Justin; Memos, Zachary (Packt Publishing, 2024)
"""Applied Fundamentals: Guess the Number"" offers a hands-on approach to learning programming by guiding participants through the creation of a simple yet captivating game. Led by Justin and Vonne, along with Zach, this course begins with an overview, setting the stage for what's to come. As learners progress, they're taken through the crucial stages of game development--from initial planning and project setup to coding game logic and user interactions. The course emphasizes the iterative process of building software, including planning, coding, testing, and refining, making it ideal for those looking to strengthen their programming foundations. Through the development of the ""Guess the Number"" game, participants will learn about user input handling, program flow control, function utilization for cleaner code, and implementing game mechanics like guess limits and win/lose determination. This course not only teaches the technical aspects of programming but also instills a problem-solving mindset, critical for any aspiring developer. By the end, learners will have a fully functional game and a deeper understanding of how to apply programming concepts in real-world projects. What you will learn Plan and set up a programming project from scratch. Handle user inputs and process them within your application. Refactor code into functions for improved readability and maintenance. Implement control flow to manage game states, including win and lose conditions. Audience This course is ideal for beginners in programming or those with basic Python knowledge looking to solidify their understanding through a practical project. A fundamental understanding of Python syntax is recommended but not mandatory. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Justin Dennison: Justin leads AWS and developer content creation for ITProTV. He has experience in multiple programming languages. His certifications include AWS Certified Solutions Architect -- Associate, AWS Certified Developer -- Associate, AWS Certified Cloud Practitioner, Oracle Certified Associate, Java SE 7 Programmer. Zachary Memos: Zachary Memos is a show host with 30+ years of on-camera experience. He brings his wit and charm to the camera while helping bring out the best in the ITProTV subject matter experts.".
Online resource; title from title details screen (O'Reilly, viewed April 23, 2024)
Keywords: Computer programming; Programmation (Informatique); computer programming; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet